Influence of University Professors on the Formation of Personal Maturity of Students. - Doskach, S., Kostyk, L., Batrynchuk, Z., Honchar, N.., Babiuk, T. ., & Skrypnyk, M. (Romaneasca Pentru Educatie Multidimensionala, 2022)
Under the influence of internal (personal) and external (social) factors, meaningful personal formations arise, that characterize this phenomenon. Thearticle explicates signs of personal maturity: at the individual level -adequate self-esteem, a high level of self-regulation, independence, and responsibility; within social interaction -the ability of the individual to be tolerant and empathic. The process of professor-student interaction in higher education institutions should be aimed at maintaining an enthusiastic attitude toward the future profession, and the development of relevant qualities and features necessary for the future specialist, which adds relevance to the study. An effective means of influencing the formation of students' personal maturity is psychological and pedagogical support for all participants of the educational process in higher education institutions, which corresponds to the natural concept of personality development in the dialectical unity of postmodern approaches to understanding the psyche. The result of such support lies in the preservation of moral, spiritual, and mental health, the promotion of emotional well-being of students, the development of natural potential, and the activation of internal resources that ensure the aspiration of a young person to self-development. The article outlines the peculiarities of the influence of university professors on the formation of students’ personal maturity. The latter is activated due to the professors’ readiness to create conditions for psychological and pedagogical support and effective organization of the education process. The prospects for further research lie in outlining methods for the development and formation of students' personal maturity within the process of professor-student interaction during distance learning and the subsequent testing of their effectiveness in the educational process
The prospects for further research lie in outlining methods for the development and formation of students' personal maturity within the process of professor-student interaction during distance learning and the subsequent testing of their effectiveness in the educational process.
Keywords: personal maturity; self-development; self-regulation; postmodernism; psychological support; pedagogical support; psychological and pedagogical support.